Strategic Leadership of Madrasah Principals in Enhancing Teacher Professionalism at School - Tuti Yulieni; Sudadi; Benny Kurniawan; Atim Rinawati; Siti Fatimah (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
The quality of education in Islamic elementary schools (Madrasah Ibtidaiyah) is highly dependent on the professionalism of educators, which in turn requires effective strategic management by school principals. to describe and analyze the formulation, implementation, and control of strategies in developing the professionalism of educators at MI KHR Ilyas Tanjungrejo Buluspesantren Kebumen. This study investigates the strategic management practices employed by the principal of MI KHR Ilyas Tanjungrejo, Kebumen, Central Java, Indonesia, in developing educator professionalism. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis from January to March 2025. Informants included the school principal, two teachers, and the school committee chair. The findings reveal three interconnected strategic management processes: (1) strategy formulation, encompassing vision-mission determination, SWOT analysis, and strategic planning through internal Teacher Working Groups (KKG), workshops, and professional training; (2) strategy implementation, involving motivational reinforcement and resource allocation, including performance rewards, seminar participation, and digital media integration; and (3) strategy control, through instructional supervision, peer observation, monitoring and evaluation by school supervisors, and mandatory teacher performance reporting. These strategic interventions resulted in measurable improvements in teacher pedagogical competence, instructional quality, and student academic achievement above the minimum competency standard. This study contributes to the growing literature on educational leadership and strategic management in Islamic educational institutions.